Muslim Occupation in France According to Arabic Literature and Western Historical Evidences - Meirison, Meirison; Rais , Zaim; Fatarib , Husnul; Muhammadi, Qasem (Journal of Al-Tamaddun, 2021)
Islam has a long history in Southern France and Italy and has contributed greatly to the formation of European civilization. This has been forgotten mainly by European and French people and Muslims in general. Driven by the Spirit of jihad and the spread of Islam, the Muslim soldiers have made France and Italy’s regions into an orderly administrative region that was previously filled up with injustice. A comparison of Arabic and Western literature, especially French and Spanish and Arabic literature, was conducted to complete this discussion. Arabic literature does not indicate in detail that Muslims have been in France for a long time based on physical evidence obtained in modern times. By conducting a literature study and a comparative historical, descriptive approach, it was found that Muslims suffered a crushing defeat in the battle with Charles Martel in Tours, October 10, 732. However, Muslims were still in Gaul, Bordeaux, and Anjou (Italy), and it took place for 250 years. This shows that Muslims could adapt to the local population. Coupled with research carried out by archaeologists, gynaecologists, and sociologists with Muslim graves’ presence in the Gaul region joined by local residents, Barbarians, and Arabs indicated that the procedure for burial was performed according to Islam. The funerals were carried out in the 7th or 9th century A.D. The history of Muslims in France and Italy is not easily forgotten; these experts’ research has perpetuated Muslims’ narrative in France and Italy.